2014
DOI: 10.1007/s10551-014-2291-8
|View full text |Cite
|
Sign up to set email alerts
|

Getting Respect from a Boss You Respect: How Different Types of Respect Interact to Explain Subordinates’ Job Satisfaction as Mediated by Self-Determination

Abstract: Interpersonal respect can be differentiated into two kinds: (1) horizontal respect, i.e. treating someone with dignity; and (2) vertical respect, i.e. genuinely honoring someone's merits. With the present research, we draw on motivation theory to explore their interplay in leadership relations. Specifically, we argue for a moderated mediation hypothesis in that (a) leaders' horizontal respect for their subordinates fundamentally speaks to subordinates' selfdetermination and (b) that the message of respectful l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 75 publications
2
39
0
Order By: Relevance
“…The first evidence pointing to this internalization process was demonstrated by research associating equality‐based respect with self‐humanization processes (Renger, Mommert, Renger & Simon, ), perceptions of personal autonomy (Renger et al, ), and self‐determination (Decker & Van Quaquebeke, ). Research has demonstrated that equality‐based respect can come from different sources including ingroups (Renger & Simon, ), outgroups (Simon, Mommert, & Renger, ), or more generally from individuals relevant in one’s life (Renger & Reese, ).…”
Section: Antecedents Of Self‐respectmentioning
confidence: 99%
“…The first evidence pointing to this internalization process was demonstrated by research associating equality‐based respect with self‐humanization processes (Renger, Mommert, Renger & Simon, ), perceptions of personal autonomy (Renger et al, ), and self‐determination (Decker & Van Quaquebeke, ). Research has demonstrated that equality‐based respect can come from different sources including ingroups (Renger & Simon, ), outgroups (Simon, Mommert, & Renger, ), or more generally from individuals relevant in one’s life (Renger & Reese, ).…”
Section: Antecedents Of Self‐respectmentioning
confidence: 99%
“…To the extent that respect is an indicator of acceptance and belonging (Bartel et al, 2012;Sleebos et al, 2006), respectful relationships should also be more satisfying. Consistent with this notion, previous research has noted a positive link between respect and relationship satisfaction (Bitran & Hoech, 1990;Frei & Shaver, 2002;Winstead, 2000), as well as greater employee/job satisfaction (Decker & Van Quaquebeke, 2014).…”
Section: Respect's Complexity and Meaningmentioning
confidence: 99%
“…In the explored literature, various views of respect were explored. Some view respect as a genuine personal attitude of treating others equally and with dignity (Decker and Van Quaquebeke, 2015). Others view respect as the identification of mutual values or interests between one another (Clarke, 2011).…”
Section: "They Are Not Giving Me the Information Unless They Like Mementioning
confidence: 99%
“…Employees or subordinates in an organisation would be inclined to follow someone perceived respectful or in a high regard (Decker and Van Quaquebeke, 2015). Hence, a manager's image and respect in the eyes of his/her subordinates, despite the JV organisational structure, is crucial for his/her influence over their performance and the performance of the joint venture.…”
Section: "They Are Not Giving Me the Information Unless They Like Mementioning
confidence: 99%
See 1 more Smart Citation